2016
DOI: 10.18632/oncotarget.8453
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine immunomodulation network dysfunction in SAMP8 mice and PrP-hAβPPswe/PS1ΔE9 mice: potential mechanism underlying cognitive impairment

Abstract: Senescence-accelerated mouse prone 8 strain (SAMP8) and PrP-hAβPPswe/PS1ΔE9 (APP/PS1) mice are classic animal models of sporadic Alzheimer's disease and familial AD respectively. Our study showed that object recognition memory, spatial learning and memory, active and passive avoidance were deteriorated and neuroendocrine immunomodulation (NIM) network was imbalance in SAMP8 and APP/PS1 mice. SAMP8 and APP/PS1 mice had their own specific phenotype of cognition, neuroendocrine, immune and NIM molecular network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…In other rodent models of premature aging, including the senescence accelerated SAMP8 mouse line (9799) and premature aging induced by d -galactose administration (100, 101), primary testicular dysfunction is associated with increased testicular ROS production. Studies by Wiley et al (30) demonstrated that CISD2-loss results in a pro-oxidative intracellular environment, which may explain the reduction in testosterone observed in CISD2-KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other rodent models of premature aging, including the senescence accelerated SAMP8 mouse line (9799) and premature aging induced by d -galactose administration (100, 101), primary testicular dysfunction is associated with increased testicular ROS production. Studies by Wiley et al (30) demonstrated that CISD2-loss results in a pro-oxidative intracellular environment, which may explain the reduction in testosterone observed in CISD2-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reduced expression and activity of proteins required for the conversion of cholesterol to testosterone, damage to steroidogenic machinery as a result of perturbation in the balance between the generation of reactive oxygen species (ROS), and their neutralization by antioxidants, is hypothesized to underlie the decreased testosterone production by aged LCs (21,23,24,94,96). In other rodent models of premature aging, including the senescence accelerated SAMP8 mouse line (97)(98)(99) and premature aging induced by D-galactose administration (100, 101), primary testicular dysfunction is associated with increased testicular ROS production. Studies by Wiley et al (30) demonstrated that CISD2-loss results in a pro-oxidative intracellular environment, which may explain the reduction in testosterone observed in CISD2-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that the NIM network is altered and dysfunctional in a PrP-hAβPPswe/PS1 ΔE9 (APP/PS1) mouse model of familial AD and early-onset AD [29, 30]. In the present study, we examined the effects of long-term oral administration of a novel Liuwei Dihuang formula (LW-AFC) on cognitive impairment, Aβ deposition, and neuronal loss in APP/PS1 mice.…”
Section: Introductionmentioning
confidence: 97%
“…2 People's Hospital Animal Ethics Committee. The hippocampal injections were performed as described previously (Wang et al, 2016). Briefly, 6-month-old mice received injection of 3 mM miRNA mimics (Genephama, Shanghai, China) into the dentate gyrus by use of a dental drill every week.…”
Section: Animals and Mirnas Hippocampal Injectionmentioning
confidence: 99%
“…Here, we chose the senescence accelerated mouse prone 8 (SAMP8) strain as an AD mouse model and the senescence-accelerated mouse-resistant 1 (SAMR1) strain as a control (Wang et al, 2016) strain. First, we measured the expression of miR-139 in the SAMP8 (AD model group) and SAMR1 mice (control group).…”
Section: Introductionmentioning
confidence: 99%